A copper / graphene composite material and its preparation method and application
By growing graphene on the surface of copper powder and combining vacuum hot-press sintering and vacuum casting technology, copper/graphene composite materials with excellent room temperature and high-temperature conductivity were prepared, which solved the problem of insufficient research on high-temperature conductivity in the prior art, and achieved efficient conductivity and strength improvement of the material at high temperature.
Patent Information
- Application Number
- CN202411412167.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-11
AI Technical Summary
In the prior art, there is little research on the high-temperature conductivity of copper graphene composite materials, and it is difficult to meet the market demand for copper materials with good high-temperature conductivity.
Copper/graphene composite materials with excellent room temperature and high temperature conductivity were prepared by chemical vapor deposition of grown graphene on the surface of a mixed powder of copper powder and nanomagnesium oxide, combined with vacuum hot press sintering and vacuum casting.
The high conductivity of copper/graphene composite materials under room temperature and high temperature conditions has been achieved, which improves its tensile strength and yield strength, and reduces energy consumption.
Smart Images

Figure CN118910457B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of high-conductivity copper materials, and in particular relates to a copper / graphene composite material and a preparation method and application thereof. Background Art
[0002] Since the discovery of electricity, pure metals have been considered to have the lowest resistivity at room temperature. This assumption defines the upper limit of electricity efficiency and determines the design size and power loss of all traditional electricity machines and equipment. The electrical conductivity of pure copper at room temperature is 5.8×10 7 S / m (100% IACS, international annealed copper standard), the conductivity of which is second only to silver among all metals (6.3×10 7 S / m), and due to their relatively low cost, copper-based materials are widely used in industrial sectors such as electronics and electrical.
[0003] With the rapid development of society and science and technology, many emerging technology fields have higher and higher requirements for conductive copper materials, and even the demand for ultra-high conductive copper, that is, a type of material with higher conductivity than pure copper, is becoming increasingly urgent. On the other hand, the world is currently facing the problems of resource shortage and global warming, and electric energy is an important form of energy transportation and conversion. If ultra-high conductive copper can be fully and successfully developed, it has the potential to significantly improve the performance of almost all electrical systems and equipment and reduce their energy consumption, which will produce huge economic and social benefits. For example, if the conductivity of ultra-high conductive copper at room temperature is more than twice that of pure copper, the weight and size of motors, transformers, wind turbines and transmission lines will be reduced to half of the current ones. Especially under high temperature conditions, the conductivity of copper materials drops sharply. The application of high-temperature conductive materials is involved in many emerging technology fields, so there is also an urgent need for copper materials with good high-temperature conductivity.
[0004] Patent document CN115351277A discloses a graphene-copper composite material and a preparation method and application thereof. The preparation method comprises S1: chemically vapor depositing copper powder under methane and a reducing atmosphere to form graphene on the surface of the copper powder to obtain a first powder, wherein the purity of the copper powder is not less than 99.8%, and the oxygen content of the copper powder is not more than 0.1%; hot pressing and sintering the first powder, and drawing and forming the graphene-copper composite material after sintering.
[0005] Patent document CN115838880A discloses a method for preparing a copper-graphene composite material, comprising: (1) using mechanical alloying to produce copper@polymer powder; (2) using cold isostatic pressing to obtain high-compactness rods; (3) further using zone melting to obtain high carbon solid solubility, regular porous rods; (4) adjusting the heat treatment mechanism so that carbon atoms in the matrix are segregated to the pore wall surface to grow graphene in situ; (5) finally obtaining conductive materials with a metallurgical bonding matrix and various specifications through hot pressing and continuous rolling.
[0006] Although much research has been conducted on the preparation of copper-graphene composite materials in the prior art, the prior art focuses more on the room temperature electrical conductivity of copper-graphene composite materials, and less on their high temperature electrical conductivity. In view of the urgent demand for copper materials with good high temperature electrical conductivity in the current market, it is of great significance to develop a new preparation process for copper-graphene composite materials and produce copper-graphene composite materials with good electrical conductivity at both room temperature and high temperature conditions. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a copper / graphene composite material and a preparation method and application thereof. The copper / graphene composite material prepared by the method of the present invention has excellent tensile strength, yield strength, room temperature conductivity and high temperature (150°C) conductivity, and can be widely used in industrial fields such as electronics and electrical engineering.
[0008] Graphene is a two-dimensional material with only one atomic layer thickness and is the material with the best electrical properties known so far. In terms of the carrier concentration and mobility of the material, graphene and copper are two types of electrical conductor materials that are significantly different but complementary. Single-layer graphene has a carrier mobility that is 4 to 5 orders of magnitude higher than that of copper, while copper has a higher carrier concentration than graphene; at the same time, copper in contact with graphene can effectively dope graphene with electrons. Therefore, the present invention obtains a copper / graphene composite material with excellent room temperature and high temperature electrical conductivity by rationally designing the preparation process of the copper / graphene composite material and by means of the composite effect and synergistic effect of the two.
[0009] The first aspect of the present invention provides a method for preparing a copper / graphene composite material, comprising the following steps:
[0010] (1) growing graphene on the surface of a mixed powder of copper powder and nano-magnesium oxide by chemical vapor deposition to obtain a copper / graphene / nano-magnesium oxide composite powder, and then removing the nano-magnesium oxide in the composite powder to obtain a copper / graphene composite powder;
[0011] (2) vacuum hot pressing and sintering the copper / graphene composite powder to obtain a copper / graphene composite preform;
[0012] (3) The copper material and the copper / graphene composite blank are melted and stirred, and then vacuum continuous casting is performed, and the obtained material is drawn and annealed to obtain the copper / graphene composite material.
[0013] Due to its chemical inertness and non-permeability, graphene can be used as a protective layer on the surface of copper powder to prevent oxidation of copper powder, thereby achieving an excellent composite interface between copper and graphene. The shear modulus of graphene is as high as 0.2 TPa. As a reinforcement, it is evenly dispersed at the copper grain boundary, which can play a role in dislocation pinning, thereby improving the strength of the composite material. The intrinsic conductivity of graphene is much higher than that of pure copper, and the temperature coefficient of resistance is lower than that of pure copper. Its uniform dispersion in the copper matrix to form a conductive network can effectively improve the conductivity of the composite material, especially the conductivity at high temperature. Therefore, controlling the uniform dispersion of graphene in the copper matrix can improve the strength and conductivity of the composite material.
[0014] The present invention grows graphene on the surface of a mixed powder of copper powder and nano-magnesium oxide by chemical vapor deposition, and cooperates with vacuum hot pressing sintering and vacuum continuous casting processes to achieve the synergy of structural integrity and uniform dispersion of graphene in the composite material, and greatly improves the bonding strength between graphene and the copper matrix, thereby improving the strength and electrical conductivity of the composite material.
[0015] Specifically, the present invention uses nano magnesium oxide powder to isolate copper powder to prevent the copper powder from sintering together during chemical vapor deposition, thereby growing high-quality (few impurities and defects, high structural integrity) and different layers of graphene on the surface of the copper powder, and after growth, the magnesium oxide can be completely removed to obtain pure copper / graphene composite powder. Afterwards, vacuum hot pressing sintering can avoid copper oxidation, greatly improve the bonding strength between graphene and copper matrix, thereby inhibiting graphene from floating during subsequent down-casting. In addition, the present invention can control the distribution density of graphene by controlling the content of graphene in the copper / graphene composite powder and the ratio of the copper / graphene composite preform to the copper material during the down-casting process, and combine stirring to make high-quality graphene uniformly and orderly dispersed in the copper matrix, forming a connected graphene network structure in the composite material as a fast channel for electron migration, thereby improving the conductivity and strength of graphene.
[0016] Preferably, in step (1), the mixed powder of copper powder and nano-magnesium oxide is obtained by mechanically mixing copper powder and nano-magnesium oxide powder.
[0017] Preferably, the particle size of the copper powder is less than 75 μm.
[0018] Preferably, the mass ratio of the copper powder to the nano magnesium oxide powder is 1:3-5. Since the density of copper is 8.96 g / cm 3 , the density of magnesium oxide is 3.58g / cm 3Therefore, the mass ratio is controlled so that the volume of the magnesium oxide powder is larger than that of the copper powder, thereby ensuring that the magnesium oxide powder can fully isolate the copper powder and prevent the copper powder from sintering together during the chemical vapor deposition process.
[0019] Preferably, the mixing condition is: uniformly mixing at a rotation speed of 2000-2500 r / min for 30-40 min. Through the above mixing, the nano magnesium oxide powder can well isolate the copper powder to prevent the copper powder from sintering into agglomerates during chemical vapor deposition.
[0020] Preferably, in step (1), the temperature of chemical vapor deposition for growing graphene is 1030-1050° C., the time is 30-40 min, and the flow rate of methane gas is 10-20 sccm.
[0021] The present invention introduces methane gas at high temperature, and under the catalytic action of copper powder, methane is decomposed into carbon atoms, and the carbon atoms form graphene on the surface of the copper powder. The decomposition temperature of methane is between 1000 and 1500°C, and the melting point of copper is 1083°C, so the growth temperature is controlled within the above range. Too small a flow rate of methane will lead to too low a growth efficiency of graphene, and too large a flow rate will result in too many impurities, defects and layers of graphene, so the methane flow rate is controlled within the above range.
[0022] The present invention controls the growth conditions of graphene within the above range, and can obtain copper / graphene composite powder with 2 to 4 graphene layers uniformly coated on the surface of copper powder and a graphene content of 0.2 to 0.8 wt.%.
[0023] The conductivity of single-layer graphene is the best, and the conductivity will deteriorate as the number of layers increases. Generally speaking, graphene with 1 to 5 layers has good conductivity; it is relatively easy to obtain graphene with this number of layers through chemical vapor deposition. Since the solid solubility of copper and carbon is close to zero and no intermediate phase can be generated, copper mainly plays a catalytic role in the whole process. Carbon atoms preferentially nucleate at the copper grain boundary to generate graphene, and then continuously deposit and connect on the copper surface to form complete graphene. When a few layers of graphene cover the surface of the copper substrate, the catalytic effect of copper is greatly suppressed, which hinders the deposition and growth of carbon atoms. Therefore, graphene with fewer layers or even a single layer can be obtained by adjusting the relevant growth parameters.
[0024] In the present invention, the content of graphene in the copper / graphene composite powder is controlled at 0.2-0.8 wt.%. If the content of graphene is too small, the copper powder cannot be completely coated, resulting in the copper in the exposed part being easily oxidized, affecting the interface bonding strength of the copper / graphene composite preform. If the content of graphene is too high, the copper catalytic effect in the later stage of chemical vapor deposition will be weakened, the number of grown graphene layers and defects will be too large, and the ability of the graphene to enhance the electrical conductivity of copper will be weakened.
[0025] Preferably, in step (1), the mixed powder of copper powder and nano-magnesium oxide is first heated to 850-900°C in an atmosphere of 300-350 sccm Ar and 50-60 sccm H2 for 50-60 minutes, then heated to 1030-1050°C in 20-30 minutes while keeping the atmosphere unchanged, and kept for 10-15 minutes before chemical vapor deposition to grow graphene. After the graphene growth is completed, the atmosphere is adjusted to 300-350 sccm Ar and 10-20 sccm H2.
[0026] Preferably, in step (1), nano-magnesium oxide in the copper / graphene / nano-magnesium oxide composite powder is removed by dilute acid, washed, and dried to obtain the copper / graphene composite powder. The present invention uses dilute acid to remove magnesium oxide in the mixed powder, and washes the residual dilute acid and magnesium salt solution and then dries to obtain pure copper powder with graphene grown on the surface, i.e., copper / graphene composite powder.
[0027] Preferably, the dilute acid includes dilute hydrochloric acid, dilute sulfuric acid, dilute nitric acid or dilute phosphoric acid.
[0028] Preferably, the mass fraction of the dilute acid is 5-10%.
[0029] Preferably, the drying temperature is 40-60°C.
[0030] Preferably, in step (2), the vacuum hot pressing sintering temperature is 850-900°C, the time is 2-4 h, the pressure is 30-50 MPa, and the vacuum degree is 10 -3 ~10 -2 The present invention avoids copper oxidation through vacuum hot pressing sintering, greatly improving the bonding strength between graphene and copper matrix, thereby inhibiting graphene from floating up in the subsequent down-drawing continuous casting process, making graphene uniformly and orderly dispersed in the copper matrix, and playing a role in dislocation pinning, thereby improving the strength of the composite material.
[0031] Preferably, in step (3), the mass ratio of the copper / graphene composite preform to the copper material is 1:3 to 9. If the ratio of the copper / graphene composite preform to the copper material is too small, the graphene dispersion density in the final composite material will be too low, and it will not be able to connect to form a conductive network, and the conductive performance will not be significantly improved; if the ratio is too large, the high-content graphene will easily agglomerate during the remelting and continuous casting process, which will deteriorate the plasticity and processing performance of the composite material.
[0032] Preferably, the copper material comprises electrolytic copper plates, copper rods, copper tubes, copper strips, copper wires, copper bars, copper rice or copper powder with a purity greater than 99.99%. The present invention uses high-purity copper material and copper / graphene composite preforms for remelting to purify the copper matrix.
[0033] The intrinsic conductivity of graphene is much higher than that of pure copper, and the temperature coefficient of resistance is lower than that of pure copper. The present invention controls the addition amount of the composite preform, thereby regulating the graphene content in the down-draw continuous casting copper / graphene composite material. The graphene is evenly dispersed and connected in the copper matrix to form a connected graphene network structure, which serves as a fast channel for electron migration, effectively improving the conductivity of the composite material, especially the conductivity at high temperature.
[0034] Preferably, in step (3), by adjusting the ratio of the copper / graphene composite preform and the copper material, the content of graphene in the obtained copper / graphene composite material is 0.02-0.2 wt.%. If the content of graphene is too low, a connected conductive network cannot be formed, and the conductive performance of the composite material is not significantly improved; if the content of graphene is too high, it will cause partial agglomeration of the graphene during the remelting and continuous casting process, which will deteriorate the plasticity and processing performance of the composite material. Therefore, the content of graphene is limited to this range.
[0035] Preferably, in step (3), the stirring is electromagnetic stirring, the frequency of the electromagnetic stirring is 20-80 Hz, and the current is 200-400 A. The present invention adopts electromagnetic stirring in the continuous casting process under vacuum to uniformly mix the copper material and the copper / graphene composite preform after melting, thereby achieving uniform dispersion of graphene in the copper matrix.
[0036] Preferably, in step (3), the vacuum degree of the vacuum continuous casting is 10 -2 ~10 -1 Pa, the protective atmosphere is Ar, the continuous casting temperature is 1100~1150℃, and the continuous casting speed is 1~10 mm / min.
[0037] Preferably, in step (3), the copper material is first melted into copper water, and then the copper / graphene composite preform is added to the copper water and kept warm, and then vacuum continuous casting is performed after the liquid level is stable. This operation can reduce the burning of graphene in the composite preform.
[0038] Preferably, the melting temperature of the copper material is 1200-1250°C, and the insulation temperature is 1100-1150°C.
[0039] Preferably, in step (3), the total processing rate of the drawing is 80-90%, and the processing rate of a single pass is 30-40%. The present invention controls the total processing rate of the drawing to fully break and elongate the copper grains, refine the grains, and regulate the distribution and orientation of graphene through large deformation. If the processing rate of a single pass is too small, the processing passes are many and the efficiency is low; if the processing rate of a single pass is too large, the product size and shape will be unqualified, or even frequently broken.
[0040] Preferably, in step (3), annealing is performed in a reducing atmosphere, the annealing temperature is 400-500°C, the annealing time is 2-4 h, and the reducing atmosphere is a mixed gas of Ar and H2, and the volume fraction of H2 in the mixed gas is 20-30%. The present invention eliminates the work hardening of the copper / graphene composite material through annealing, so that the fibrous grains are recrystallized into equiaxed grains, and the plasticity, bendability and fatigue resistance are improved. In addition, the reducing atmosphere can prevent the copper / graphene composite material from being oxidized during the annealing process, thereby improving the surface quality of the product.
[0041] The second aspect of the present invention provides a copper / graphene composite material prepared by the above preparation method. The copper / graphene composite material of the present invention has high tensile strength, yield strength, and excellent room temperature electrical conductivity and high temperature electrical conductivity, which can significantly improve the efficiency of metal electrical and electronic applications and save energy.
[0042] Preferably, the room temperature conductivity of the copper / graphene composite material is above 102% IACS, the conductivity at 150° C. is above 71% IACS, the tensile strength is above 325 MPa, and the yield strength is above 300 MPa.
[0043] The third aspect of the present invention provides the application of the copper / graphene composite material as a high-temperature conductive material in the fields of new energy, electronic appliances, aerospace, etc. The copper / graphene composite material with high-temperature conductivity of the present invention can be applied to key components in high-temperature service scenarios such as new energy drive motors, thereby improving their performance, efficiency and endurance, and reducing costs. In addition, the copper / graphene composite material of the present invention also has good plasticity and fatigue resistance to meet the requirements of cold and hot deformation, and is easy to be processed into products of various shapes to meet application scenarios such as easy-to-bend and easy-to-wind wires that have certain requirements for softness.
[0044] Compared with the prior art, the present invention has at least the following beneficial effects:
[0045] (1) The present invention uses nano-magnesium oxide powder to isolate copper powder to prevent the copper powder from sintering together during the chemical vapor deposition process, thereby growing high-quality graphene with different numbers of layers on the surface of the copper powder, and after the growth, the magnesium oxide can be completely removed to obtain pure copper / graphene composite powder. Subsequently, vacuum hot pressing sintering can be performed to avoid copper oxidation, greatly improve the bonding strength between graphene and the copper matrix, and thus inhibit the floating of graphene during the subsequent downward continuous casting process. In addition, the present invention can control the distribution density of graphene by controlling the content of graphene in the copper / graphene composite powder and the ratio of the copper / graphene composite blank to the copper material during the downward continuous casting process, and combine stirring to make the high-quality graphene evenly and orderly dispersed in the copper matrix, forming a connected graphene network structure in the composite material, which serves as a fast channel for electron migration, thereby improving the conductivity and strength of the graphene;
[0046] (2) The copper / graphene composite material of the present invention has high tensile strength, yield strength, and excellent room temperature electrical conductivity and high temperature electrical conductivity. Its electrical conductivity at 150°C is above 71% IACS, which is of great significance for improving the efficiency of metal electrical and electronic applications and saving energy. The copper / graphene composite material of the present invention can also be further processed into large-sized rods, wires, plates and strips and other products to achieve industrial production. As a high-temperature conductive material, it is widely used in the fields of new energy, electronic appliances, aerospace, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 is the SEM image of the copper / graphene composite material in Example 3 ( Figure 1 (a) of the diagram) and the corresponding EDS-mapping element diagram ( Figure 1 Part (b) and Figure 1 (c) of the .
[0048] Figure 2 This is a TEM image of graphene extracted after full corrosion of the copper / graphene composite material in Example 3. DETAILED DESCRIPTION
[0049] The technical solution of the present invention is clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0050] The present invention provides 3 embodiments and 1 comparative example. Example 1
[0051] The copper / graphene composite material with a graphene content of 0.05 wt.% is prepared, specifically comprising the following steps:
[0052] (1) using a high-speed mixer at a speed of 2000 rpm to uniformly mix copper powder with a particle size of less than 75 μm and nano-magnesium oxide powder in a mass ratio of 1:5 for 30 min to obtain a mixed powder of copper powder and nano-magnesium oxide;
[0053] (2) The mixed powder of copper powder and nano-magnesium oxide is loaded into a quartz tube, and then placed in a tube furnace, and heated to 900°C in an atmosphere of 300 sccm Ar and 50 sccm H2 for 60 minutes, and then kept unchanged, heated to 1050°C for 20 minutes, and kept for 10 minutes before starting to grow; during the growth stage, methane gas is used as a carbon source to grow graphene, with a flow rate of 20 sccm and a growth time of 30 minutes. After the growth is completed, the atmosphere is changed to 300 sccm Ar and 15 sccm H2. After the furnace is cooled to room temperature, the powder is taken out and ground and dispersed, and the magnesium oxide in the mixed powder is removed with 10% mass fraction of dilute hydrochloric acid, and the residual hydrochloric acid and magnesium chloride solution are removed with deionized water. Finally, it is dried in a drying oven at 50°C to obtain pure copper powder with graphene grown on the surface, that is, copper / graphene composite powder, wherein the content of graphene in the copper / graphene composite powder is 0.4 wt.%;
[0054] (3) The copper / graphene composite powder was loaded into a graphite mold of a hot press and sintered under vacuum hot pressing at 900 °C for 3 h, with a pressure of 40 MPa and a vacuum degree of 10 -2 Pa, the graphite mold and the powder are separated by graphite paper for demoulding, and the surface is milled after cooling in the furnace to obtain the copper / graphene composite blank for use;
[0055] (4) Add 5 kg of electrolytic copper plate into the crucible of the down-draw continuous casting furnace and evacuate to 10 -1 After the electrolytic copper plate is completely melted, the content of graphene in the composite blank is calculated according to the mass of the copper powder before and after chemical vapor deposition, and the copper / graphene composite blank is added according to the graphene content of 0.05 wt.% in the composite material (the mass ratio of the copper / graphene composite blank to the electrolytic plate in this embodiment is 1:7), and then electromagnetic stirring is performed, the stirring frequency is 50 Hz, and the stirring current is 280 A. Then, the temperature is kept at 1120°C, and after the liquid level is completely stable, the traction system is started, and the downward continuous casting is performed at a speed of 5 mm / min;
[0056] (5) subjecting the material obtained in step (4) to drawing deformation with a total processing rate of 90% and a single-pass processing rate of 30%;
[0057] (6) The copper / graphene composite material was annealed at 450 °C for 4 h in a reducing atmosphere of 20% H2 and the balance Ar. Example 2
[0058] The copper / graphene composite material with a graphene content of 0.1 wt.% is prepared, specifically comprising the following steps:
[0059] (1) using a high-speed mixer at a speed of 2000 rpm to uniformly mix copper powder with a particle size of less than 75 μm and nano-magnesium oxide powder in a mass ratio of 1:5 for 30 min to obtain a mixed powder of copper powder and nano-magnesium oxide;
[0060] (2) The mixed powder of copper powder and nano-magnesium oxide was loaded into a quartz tube, and then placed in a tube furnace, and heated to 900°C in an atmosphere of 300 sccm Ar and 50 sccm H2 for 60 minutes, and then kept the atmosphere unchanged, heated to 1050°C for 20 minutes, and then started to grow after 10 minutes; during the growth stage, methane gas was used as a carbon source to grow graphene, with a flow rate of 20 sccm and a growth time of 35 minutes. After the growth was completed, the atmosphere was changed to 300 sccm Ar and 15 sccm H2. After the furnace was cooled to room temperature, the powder was taken out and ground and dispersed, and the magnesium oxide in the mixed powder was removed with 10% dilute hydrochloric acid by mass, and the residual hydrochloric acid and magnesium chloride solution were removed with deionized water. Finally, it was dried in a drying oven at 50°C to obtain pure copper powder with graphene grown on the surface, that is, copper / graphene composite powder, wherein the content of graphene in the copper / graphene composite powder was 0.6 wt.%;
[0061] (3) The copper / graphene composite powder was loaded into a graphite mold of a hot press and sintered under vacuum hot pressing at 900 °C for 3 h, with a pressure of 40 MPa and a vacuum degree of 10 -2 Pa, the graphite mold and the powder are separated by graphite paper for demoulding, and the surface is milled after cooling in the furnace to obtain the copper / graphene composite blank for use;
[0062] (4) Add 5 kg of electrolytic copper plate into the crucible of the down-draw continuous casting furnace and evacuate to 10 -1 After the electrolytic copper plate is completely melted, the content of graphene in the composite blank is calculated according to the mass of the copper powder before and after chemical vapor deposition, and the copper / graphene composite blank is added according to the graphene content of 0.1 wt.% in the composite material (the mass ratio of the copper / graphene composite blank to the electrolytic plate in this embodiment is 1:5), and then electromagnetic stirring is performed, the stirring frequency is 50 Hz, and the stirring current is 280 A. Then, the temperature is kept at 1120°C, and after the liquid level is completely stable, the traction system is started, and the downward continuous casting is performed at a speed of 5 mm / min;
[0063] (5) subjecting the material obtained in step (4) to drawing deformation with a total processing rate of 90% and a single-pass processing rate of 30%;
[0064] (6) The copper / graphene composite material was annealed at 450 °C for 4 h in a reducing atmosphere of 20% H2 and the balance Ar. Example 3
[0065] The copper / graphene composite material with a graphene content of 0.2 wt.% is prepared, specifically comprising the following steps:
[0066] (1) using a high-speed mixer at a speed of 2000 rpm to uniformly mix copper powder with a particle size of less than 75 μm and nano-magnesium oxide powder in a mass ratio of 1:5 for 30 min to obtain a mixed powder of copper powder and nano-magnesium oxide;
[0067] (2) The mixed powder of copper powder and nano-magnesium oxide is loaded into a quartz tube, and then placed in a tube furnace, and heated to 900°C in an atmosphere of 300 sccm Ar and 50 sccm H2 for 60 minutes, and then kept unchanged, heated to 1050°C for 20 minutes, and kept for 10 minutes before starting to grow; during the growth stage, methane gas is used as a carbon source to grow graphene, with a flow rate of 20 sccm and a growth time of 40 minutes. After the growth is completed, the atmosphere is changed to 300 sccm Ar and 15 sccm H2. After the furnace is cooled to room temperature, the powder is taken out and ground and dispersed, and the magnesium oxide in the mixed powder is removed with 10% mass fraction of dilute hydrochloric acid, and the residual hydrochloric acid and magnesium chloride solution are removed with deionized water. Finally, it is dried in a drying oven at 50°C to obtain pure copper powder with graphene grown on the surface, that is, copper / graphene composite powder, wherein the content of graphene in the copper / graphene composite powder is 0.8 wt.%;
[0068] (3) The copper / graphene composite powder was loaded into a graphite mold of a hot press and sintered under vacuum hot pressing at 900 °C for 3 h, with a pressure of 40 MPa and a vacuum degree of 10 -2 Pa, the graphite mold and the powder are separated by graphite paper for demoulding, and the surface is milled after cooling in the furnace to obtain the copper / graphene composite blank for use;
[0069] (4) Add 5 kg of electrolytic copper plate into the crucible of the down-draw continuous casting furnace and evacuate to 10 -1After the electrolytic copper plate is completely melted, the content of graphene in the composite blank is calculated according to the mass of the copper powder before and after chemical vapor deposition, and the copper / graphene composite blank is added according to the graphene content of 0.2 wt.% in the composite material (the mass ratio of the copper / graphene composite blank to the electrolytic plate in this embodiment is 1:3), and then electromagnetic stirring is performed, the stirring frequency is 50 Hz, and the stirring current is 280 A. Then, the temperature is kept at 1120°C, and after the liquid level is completely stable, the traction system is started, and the downward continuous casting is performed at a speed of 5 mm / min;
[0070] (5) subjecting the material obtained in step (4) to drawing deformation with a total processing rate of 90% and a single-pass processing rate of 30%;
[0071] (6) The copper / graphene composite material was annealed at 450 °C for 4 h in a reducing atmosphere of 20% H2 and the balance Ar.
[0072] Comparative Example 1
[0073] A pure copper material with a graphene content of 0 wt.% was prepared as a comparison sample by the same vacuum continuous casting process, which specifically includes the following steps:
[0074] (1) Add 5 kg of electrolytic copper plate into the crucible of the down-draw continuous casting furnace and evacuate to 10 -1 After the temperature reaches 1000 °C, Ar is introduced, and then the temperature is raised to 1250 °C to melt the electrolytic copper plate. After the electrolytic copper plate is completely melted, electromagnetic stirring is performed with a stirring frequency of 50 Hz and a stirring current of 280 A. Then, the temperature is kept at 1120 °C. After the liquid level is completely stable, the traction system is started, and the downward continuous casting is performed at a speed of 5 mm / min to obtain a pure copper comparison sample;
[0075] (2) The pure copper sample was subjected to drawing deformation with a total processing rate of 90% and a single-pass processing rate of 30%;
[0076] (3) Annealing at 450 °C for 4 h in a reducing atmosphere of 20% H2, balance Ar.
[0077] Table 1 shows the graphene layer number, content, mechanical and electrical properties of the copper / graphene composite material in the embodiment and the pure copper material in the comparative example. Compared with comparative example 1, copper powder with different number of covering layers and different content of graphene was obtained in the embodiment by controlling the growth conditions. Subsequently, a copper / graphene composite blank was obtained by vacuum hot pressing sintering, and a copper / graphene composite material with uniformly dispersed graphene was prepared by vacuum bottom drawing continuous casting. After that, a copper / graphene composite material with excellent tensile strength, yield strength, room temperature conductivity and high temperature (150°C) conductivity was obtained by drawing and annealing.
[0078] Table 1 Mechanical and electrical properties of copper / graphene composites and pure copper materials
[0079]
[0080] Figure 1 The SEM image and the corresponding EDS-mapping element map of the copper / graphene composite material in Example 3 are shown, showing that it is mainly composed of Cu and C elements. The copper matrix of the copper / graphene composite material in Example 3 is completely corroded using concentrated nitric acid, and the extraction product is obtained by filtration. The TEM image of the product is as follows: Figure 2 As shown, lamellar graphene can be observed.
Claims
1. A method for preparing a copper / graphene composite material, characterized in that: The following steps are involved: (1) growing graphene on the surface of a mixed powder of copper powder and nano-magnesium oxide by chemical vapor deposition to obtain a copper / graphene / nano-magnesium oxide composite powder, and then removing the nano-magnesium oxide in the composite powder to obtain a copper / graphene composite powder, wherein the content of graphene in the copper / graphene composite powder is 0.2-0.8 wt.%; (2) vacuum hot pressing and sintering the copper / graphene composite powder to obtain a copper / graphene composite preform; (3) The copper material and the copper / graphene composite preform are melted and stirred, and then vacuum drawn continuous casting is performed, and the obtained material is drawn and annealed to obtain the copper / graphene composite material, wherein the mass ratio of the copper / graphene composite preform to the copper material is 1:3-9, and the room temperature conductivity of the copper / graphene composite material is above 102% IACS, and the conductivity at 150°C is above 71% IACS.
2. The preparation method according to claim 1, characterized in that: The mixed powder of copper powder and nano-magnesium oxide is obtained by mixing nano-magnesium oxide powder and copper powder with a particle size less than 75 μm at a rotation speed of 2000-2500 r / min for 30-40 min, wherein the mass ratio of the copper powder to the nano-magnesium oxide powder is 1:3-5.
3. The preparation method according to claim 1 or 2, characterized in that: The temperature of the chemical vapor deposition growth graphene is 1030-1050°C, the time is 30-40 minutes, and the flow rate of the methane gas is 10-20 sccm.
4. The preparation method according to claim 3, characterized in that: Nano magnesium oxide in the composite powder is removed by using dilute acid, wherein the dilute acid includes dilute hydrochloric acid, dilute sulfuric acid, dilute nitric acid or dilute phosphoric acid, and the mass fraction of the dilute acid is 5-10%.
5. The preparation method according to claim 4, characterized in that: The vacuum hot pressing sintering temperature is 850-900°C, the time is 2-4 h, the pressure is 30-50 MPa, and the vacuum degree is 10 -3 ~10 -2 Pa.
6. The preparation method according to claim 5, characterized in that: The copper material includes electrolytic copper plates, copper rods, copper tubes, copper strips, copper wires, copper bars, copper rice or copper powder with a purity greater than 99.99%.
7. The preparation method according to claim 6, characterized in that: The vacuum degree of the vacuum continuous casting is 10 -2 ~10 -1 Pa, the continuous casting temperature is 1100~1150℃, and the continuous casting speed is 1~10 mm / min.
8. The preparation method according to claim 7, characterized in that: In step (3), the stirring is electromagnetic stirring, the frequency of the electromagnetic stirring is 20-80 Hz, and the current is 200-400 A.
9. The preparation method according to claim 8, characterized in that: In step (3), the copper material is first melted into copper water, and then the copper / graphene composite blank is added to the copper water and kept warm. After the liquid level is stable, vacuum continuous casting is performed.
10. The preparation method according to any one of claims 4 to 9, characterized in that: The total processing rate of the drawing is 80-90%, and the single-pass processing rate is 30-40%.
11. The preparation method according to claim 10, characterized in that: The annealing is carried out in a reducing atmosphere at a temperature of 400-500° C. for a time of 2-4 h, wherein the reducing atmosphere is a mixed gas of Ar and H 2 , and the volume fraction of H 2 in the mixed gas is 20-30%.
12. The preparation method according to claim 11, characterized in that: In the copper / graphene composite material, the content of graphene is 0.02-0.2 wt.%.
13. The copper / graphene composite material prepared by the preparation method according to any one of claims 1 to 12.
14. Application of the copper / graphene composite material according to claim 13 as a high-temperature conductive material in the fields of new energy, electronic appliances or aerospace.
Citation Information
Patent Citations
Graphene copper composite material and preparation method and application thereof
CN115351277A
Preparation method of copper-graphene composite material
CN115838880A
Processing technology of high-conductivity and high-strength copper rod
CN114101369A